Impact of Heuristic Behavior and Risk Perception on Investment Decisions by Young Investors - Mawaddah, Nor; Oktaviani, Ayu (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This research examines how young investors' heuristic behaviour and risk perception influence their decision-making in investments within the Faculty of Economics and Business at Lambung Mangkurat University. The variables under investigation in this study include heuristic behaviour and risk perception as independent factors, with investment decision-making as the dependent variable. The study population encompassed 2,901 students in the Faculty of Economics and Business at Lambung Mangkurat University. The sample size was determined through purposive sampling, resulting in a final sample of 66 participants with investment experience. Primary data was collected via a questionnaire. The analysis employed multiple linear regression using the SPSS version 26 software. The findings demonstrate that heuristic behaviour and risk perception significantly influence investment decision-making. The implication of this research is to provide an understanding that it is essential to consider fundamental and technical analysis in investment decisions